PERAN GURU AGAMA DALAM MENGATASI KESULITAN MEMBACA AL-QUR’AN (STUDI KASUS DI MTS NEGERI 2 BIMA) - Muhammad Miftahul Maulana; Muhammad Sulistiono; Moh. Eko Nasrulloh (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Education in schools can not be separated from the problems of students in reading the Qur'an, this is due to the background of students from general education, therefore, MTs Negeri 2 Bima school seeks to improve the quality of education by providing learning programs to read the Qur'an 'an through the empowerment of religious teachers so that religious teachers play an important role in guiding and teaching in certain ways. So the author wants to know how the efforts of religious teachers in overcoming the difficulties of reading the Qur'an, the difficulties experienced by students, as well as the factors supporting and inhibiting the efforts of religious teachers. The position of the author in this study as a participant observer is to participate in the group and declare himself as an observer. The data collection technique uses the observation method, which is a way of collecting data by observing the ongoing activities, the interview method is collecting data with a direct question and answer process with the resource person, and the documentation method, which is collecting data from records of events that have passed in the form of pictures and writings such as diaries. The results of the research show that the efforts of religious teachers are through teaching in the classroom by applying the habit of reading short suras, teaching recitation of tajwid with the lecture, question and answer method, and drill, in addition to being a BTQ coach by using the iqra' method through the media of the Qur'an. and iqra books, then evaluate learning. In addition, the religious teacher is also an imtaq builder who is responsible for overseeing the running of activities in which there is a recitation of the Qur'an in the hope that students will get used to reading fluently.Â Kata kunci: Guru Agama, Kesulitan Membaca Al-Qurâ€™an